PENGARUH QUICK RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURN OVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA (Studi Pada Perusahaan Pertambangan Sub Sektor Batubara yang Terdaftar di BEI tahun 2014-2017) - Yayuk Retnowati; Jeni Susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe purpose of this study was to determine how the Quick Ratio, Debt to Equity Ratio, Total Asset Turn Over and Net Profit Margin had an effect on earnings growth.This research uses quantitative research. The selection of this research sample uses Purposive Sampling techniques using several criteria. And selected 10 coal sub-sector mining companies listed on the Indonesia Stock Exchange in 2014-2017. Analysis of the data used is multiple linear regression analysis.The results of this study that Quick Ratio, Debt to Equity Ratio, Total Asset Turn Over did not affect earnings growth. While Net Profit Margin has an effect on earnings growth. And it can be concluded that the Quick Ratio, Debt to Equity Ratio, Total Asset Turn Over and Net Profit Margin jointly influence earnings growth. Keywords: Quick Ratio, Debt to Equity Ratio, Total Asset Turn Over, Net Profit Margin and Earnings Growth.